Verifying chloride penetration in concrete test samples partially immersed in seawater in Recife, Pernambuco - Berenguer, Romildo; Passos, Adriana; Monteiro, Eliana; Helene, Paulo; Just, Ángelo; Oliveira, Romilde; Medeiros, Marcelo; Carneiro, Arnaldo (Revista ALCONPAT, 2018)
The objective of this research is to analyze, using chemical tests, the quantity of chloride ions in concretes with different traces (proportions of materials) in their depths. To do so, tests were performed in laboratories, and test samples were made with partial immersion in seawater, in accordance with the standards and Mohr method. The results confirmed that the penetration percentage of chloride ions is less for the rich trace, in relation to the others test samples studied. Accordingly, it is concluded that the stronger the concrete the greater the penetration resistance of chloride ions, but these results are to be expected, since the concrete with greatest strength and same materials tends to hinder the entry of those ions.